The individual and sequential effect of focused attention and open monitoring meditation on mindfulness skills - Haruyuki Ishikawa; Toshizumi Muta; Tetsuri Abe; Nozomi Imajo; Fusako Koshikawa (PLoS ONE, 2025)
Mindfulness meditation has two components: focused attention (FA) meditation and open-monitoring (OM) meditation. Based on traditional Buddhist principles, it is recommended that FA meditation be practiced prior to OM meditation. However, the influence of the order in which these meditations are practiced on the efficacy of interventions has not yet been empirically investigated. This study examined the effects of the order of FA and OM meditation on the level and process of acquiring mindfulness skills. Thirty-three Japanese undergraduate and graduate students who were meditation novices completed the intervention. Participants were assigned to three groups: the group practicing 4-week FA meditation prior to 4-week OM meditation (FA-OM group), the group practicing meditation in reverse order (OM-FA group), and the wait-list control group. Each meditation training session consisted of one 1-hour group session per week and a 15-min daily homework. All participants were assessed for trait mindfulness once a week. The results showed that the FA-OM group scored higher than the control group for most mindfulness skills. In addition, awareness, describing, acceptance, and observing skills increased earlier in the FA-OM group than in the OM-FA group. However, the skill of staying aware at the present moment increased earlier in the OM-FA group than in the FA-OM group. These results suggest that the order of practicing the two meditations primarily influences the process of acquiring mindfulness skills rather than the level of skills, and that it is reasonable to practice FA meditation prior to OM meditation to cultivate mindfulness skills for novices.